Analisis Kausalitas Ketimpangan Pendapatan, Korupsi dan Kemiskinan di Negara Lower Middel Income Asean - Novilia Hartisa; Dewi Zaini Putri (Universitas Negeri Padang, 2021)
This study is to see whether there is a causal relationship between income inequality, corruption and poverty in ASEAN countries. This study uses a panel of data in five lower middle income countries in ASEAN from 2010-2018, using the Vector Auto Regression (PVAR) processing method. From the results of the investigation that: (1) There is a causality relationship between income inequality and corruption in the five lower middle income countries in ASEAN, (2) There is no causality relationship between income inequality and poverty in the five lower middle income countries in ASEAN, but only there is a one-way relationship of income and corruption in five lower middle income countries in ASEAN, (3) There is no causal relationship between corruption and poverty either one way or reciprocally in five lower middle income countries in ASEAN.S